2015
DOI: 10.11138/gchir/2015.36.3.101
|View full text |Cite
|
Sign up to set email alerts
|

Surgical drain after open or laparoscopic splenectomy: is it needed or contraindicated?

Abstract: The use of surgical drain after abdominal surgery has always been a controversial issue.Benefits and risks related to the operatively placed drains in the abdominal cavity have been discussed since a hundred years ago when some surgeons where in favor of the drainage, while skeptic others considered not physiological their use (1, 2).In the common practice intra-abdominal drains have been used to help the surgeons in the post-operative phase to identify post-operative bleeding, to drain and monitor residual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
(30 reference statements)
1
6
0
2
Order By: Relevance
“…Moreover, serous appearance of the exudates at the insertion point of the drain was also related to the detection of a pathogen. In light of our results and the results of Vecchio et al [13] and Fan et al [30], we dare to recommend that implants should be removed as soon as appearance at the insertion point becomes serous. Early removal of the drains plays an important role in diminishing incidence of abdominal infections [13,30].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Moreover, serous appearance of the exudates at the insertion point of the drain was also related to the detection of a pathogen. In light of our results and the results of Vecchio et al [13] and Fan et al [30], we dare to recommend that implants should be removed as soon as appearance at the insertion point becomes serous. Early removal of the drains plays an important role in diminishing incidence of abdominal infections [13,30].…”
Section: Discussionsupporting
confidence: 51%
“…At the present time, little information exists in the literature about their usefulness, and the use of abdominal drainage after surgery is, therefore, often dogmatic. Some surgeons have reported that their use is associated with complications as a risk of ascending infections [13,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration stay, volume and content of the drainage are significantly shorter if the hemostasis is made by devices after liver resection (10). The fibrin sealant after liver resection is effective in decreasing drainage's volume, postoperative blood transfusion, complications and hospital stay (11).…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…Гемостаз центральных разрывов селезенки при помощи препарата Тахокомб осуществлять не следует, так как в этом случае велика опасность вторичного кровотечения. В данной ситуации выполняется спленэктомия [6].…”
unclassified